Level of resilience and family functionality in adolescents in a shelter in Ventanilla, Peru - Choque Medrano, Edith (2018)
Objectives: To determine the relationship between the level of resilience and family functionality in adolescents of the Ventanilla shelter, Peru. Material and Methods: The study approach is quantitative, the design is non-experimental, correlational and cross-sectional. The population consisted of 160 adolescents residing in the shelter. The instruments used were the Connor-Davidson resilience scale (CD-RISC) and the family APGAR questionnaire. Results: In relation to the level of resilience, the average level predominated (52.5%), followed by the high level (46.9%) and low level (0.6%). The dimension of resilience that presented the highest percentage of high level of resilience was control and purpose (61.9%), the one that presented the highest percentage of low level of resilience was spirituality (8.1%). Regarding family functionality, families with mild dysfunction predominated (33.1%), followed by moderate dysfunction (28.8%), good function (25.6%) and severe dysfunction (12.5%). The statistical test of bivariate Spearman correlation shows a correlation coefficient of 0.349 (p <0.01), that is, the main variables of the study resilience and family functionality, have a moderate proportional relationship with a margin of error of 0.01 (1%). Conclusions: The predominant level of resilience was the means. In terms of family functionality, families with mild dysfunction predominated. The variable resilience and family functionality present a directly proportional moderate relationship.